2018
DOI: 10.1007/s12289-018-1415-6
|View full text |Cite
|
Sign up to set email alerts
|

Coupled effects of initial orientation scatter and grain-interaction to texture evolution: a crystal plasticity FE study

Abstract: Coupled effects of initial orientation scatter and grain-interaction to texture Coupled effects of initial orientation scatter and grain-interaction to texture evolution: a crystal plasticity FE study evolution: a crystal plasticity FE study Abstract Abstract Grain orientation and neighbourhood are two main factors that determine the in-grain and global texture. The coupled effects of them to texture evolution has not been well understood. In this work, initial orientations scattered from exact Cube at four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In comparison to the element rotation, the material rotation has an effect on the deformation and is relevant for the texture due to its influence on the grain orientation [124][125][126]. Figure 8 illustrates the source of the material rotation.…”
Section: Element and Materials Rotationmentioning
confidence: 99%
“…In comparison to the element rotation, the material rotation has an effect on the deformation and is relevant for the texture due to its influence on the grain orientation [124][125][126]. Figure 8 illustrates the source of the material rotation.…”
Section: Element and Materials Rotationmentioning
confidence: 99%
“…The hardening model and material parameters are described in Appendix B. This CPFEM model and the set of material parameters have been used in prior research to investigate texture evolution after different rolling processes [3,18], and accurate predictions have been obtained. Figure 2a shows an inverse pole figure (IPF) and high angle grain boundaries (HAGBs) EBSD map after 1-ARB.…”
Section: Texture Modellingmentioning
confidence: 99%
“…AZ31 is one of the most widely applied variants among Mg alloys. Experimental studies showed that the initial texture in the forming process of Mg alloy has a remarkable effect on its material properties [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%